Factors Influencing on Students’ Learning Problem at Primary School in Phonthong District, Luang Prabang Province: https://doi.org/10.69692/SUJMRD0901329 - Silivanh, Sommay; Thipphaphone, Kinnaly; Chanhthahong, Khamxay; Khotsaignoh, Saiphone; Vongvilay, Chanpheng (Souphanouvong University Journal Multidisciplinary Research and Development, 2023)
This research focuses on factors as problems influencing student learning quality at primary school in Phonthong District, Luang Prabang province. The objective included 1) the level of importance of the problems to the student’s learning quality at primary school in Phonthong District, Luang Prabang province, and 2) factors as problems influencing student learning quality at primary school in Phonthong District, Luang Prabang province. The study was conducted with 25 primarry school and 535 primary students from grade 3 to grade 5. This quantitative research utilized questionnaires for data collection and the data were analyzed using the descriptive statistic by Program SPSS and inferential statistics by Program MATLAB. The results that the condition of learning problems of primary school students in Grade 3 - Grade 5 in Phonthong District, Luang Prabang Province as a whole is a moderate level of problems such as student's personal, academic behavior, parents' attention to the student's education, the location of the school, the relationship between students and friends in the classroom, the relationship between the student and the teacher and the teacher's behavior towards the student as a whole are moderate level. So, the most problematic factors for primary school students are the parents' attention to the students' learning, the teacher's behavior towards the students, the student's learning habits, the school's location factor, the relationship between the students and the teacher, the relationship between the students and their friends in the class and finally the personality factors of the students respectively.